Highly Efficient One-Step Conversion of Fructose to Biofuel 5-Ethoxymethylfurfural Using a UIO-66-SO3H Catalyst - Zhao, Kangyu; Xiang, Yanping; Sun, Xiaoao; Chen, Linjiao; Xiao, Jiafu; Liu, Xianxiang (Frontiers in Chemistry, 2022)
In this study, a novel sulfonic acid-modified catalyst for MOFs (UIO-66-SO3H) was synthesized using chlorosulfonic acid as a sulfonating reagent and first used as efficient heterogeneous catalysts for the one-pot conversion of fructose into biofuel 5-ethoxymethylfurfural (EMF) in a cosolvent free system. The physicochemical properties of this catalyst were characterized by Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), and powder X-ray diffraction (XRD). The characterization demonstrated that the sulfonic acid group was successfully grafted onto the MOF material and did not cause significant changes to its morphology and structure. Furthermore, the effects of catalyst acid amount, reaction temperature, reaction time, and catalyst dosage on reaction results were investigated. The results showed that the conversion of fructose was 99.7% within 1 h at 140°C, while the EMF yield reached 80.4%. This work provides a viable strategy by application of sulfonic acid-based MOFs for the efficient synthesis of potential liquid fuel EMF from renewable biomass.